Dry and Wet Wear Rate Determination of Steel and Kovar Alloys - Kadhim Judran, Hadia (Al-Nahrain Journal of Science, 2020)
Two types of alloy (Steel and Kovar) were prepared and machined as half ring. Wear testing system was used to determine the wear rate of specimens without any lubrication, and after modified wear testing system which was used to test the specimen under lubricant condition. The wear rate was determined by using weighing method and then calculated. The results shows the values of wear rate of kovar specimens are higher than the values of wear rate for steel specimens in both two cases with and without lubrication. The result of wear rates were plotted as function of sliding time at a fixed normal load.